2008
DOI: 10.1308/003588408x242033
|View full text |Cite
|
Sign up to set email alerts
|

Recent Changes in the Management of Blunt Splenic Injury: Effect on Splenic Trauma Patients and Hospital Implications

Abstract: Ann R Coll Surg Engl 2008; 90: 109-112 109Until recently, the accepted treatment for splenic trauma, even for minor injuries, used to be splenectomy. This aggressive approach was based on the belief that, in adulthood, the spleen does not contribute any major function and conservative treatment was associated with potential life-threatening haemorrhage. With increasing recognition of the spleen's role in immunological function and awareness of overwhelming postsplenectomy sepsis (OPSI), there has been an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 17 publications
6
23
0
1
Order By: Relevance
“…15 Arlet et al found 28% of the patient with blunt trauma abdomen presenting with vomiting. 7 In the present series 4 (13.33%) patients presented with shock. Shock was either due to hypovolemia or reflex due to severe pain or apprehension.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…15 Arlet et al found 28% of the patient with blunt trauma abdomen presenting with vomiting. 7 In the present series 4 (13.33%) patients presented with shock. Shock was either due to hypovolemia or reflex due to severe pain or apprehension.…”
Section: Discussionmentioning
confidence: 41%
“…2 Arlet et al found male-female incidence of 77.02% and 22.08% respectively. 7 The higher incidence of splenic trauma in male is due to the fact that, the males are more exposed to trauma because of their outdoor works. But in west this difference is relatively narrow In the present study the most common cause of blunt splenic trauma was found to be motor vehicle accident, accounting for 46.66% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other risks may result from strategies aimed at splenic preservation, mainly the use of angiography (ANGIO) and embolization (EMBO). Patients may experience exposure to radiation, invasive procedures, and increased costs as a result of guidelines and treatment algorithms aimed at splenic preservation (15,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Trauma patients with isolated splenic injuries are the best indication group for the prognosis (33,34). The mortality rate in these patients varies between 2 to 9.3%and the lowest mortality rates are seen after splenectomy due to these indications (35,37).…”
Section: Discussionmentioning
confidence: 99%